Preliminary diagnosis of environmental costs at an industrial unit of a food sector company in Passo Fundo, RS - Brandli, Elisangela Nicoloso; Pandolfo, Adalberto; González, Marco Aurélio; Reinehr, Renata; Guimarães, Jalusa; Barbisan, Ailson (Revista Gestão da Produção Operações e Sistemas, 2008)
This article presents a preliminary diagnosis of the decurrent ambient costs of the productive process of a foodcompany.. The work was carried through from bibliographical revisions, to identify to the variable and pointersrelated to the ambient costs and to define the methodology to be applied throughout the research. Anotherused strategy in had been visits leases, as well as interviews not structuralized and analyses of reports of exit ofresidues, ambient reports of identification of aspects and impacts, reports of ambient pointers and flowchartsof the productive process, disponibilizados for the company. The results gotten until the moment indicate thatthe countable system used by the company does not present pointers adjusted for the effective control of theinvestments and expenses in the area of the environment. For the scientific community the present study it willbring greater knowledge on ambient costs, giving subsidies to other companies of as to proceed in the identificationprocess of its ambient costs, since still it is data little explored in Brazil and has few research related tothe subject.Keywords: Productive process. Decision making. Countable system. Methodology Jasch.